VISUAL-EMOTIONAL ELEMENTS OF FOLK DANCE IN THE STRUCTURE OF PUPILS' WRITING - Jovanović, Aleksandar M (Sinteze - časopis za pedagoške nauke , književnost i kulturu, 2017)
Familiarizing the pupils with the concept of folk dance. Folk dance as a part of folk lore. The elements of folk dance (music, song, costume, coreography). Observing integral elements. Syncretism. Describing observed and experienced phenomena. Description of dynamic artistic image. Description of folk dance introduces pupils for observation and appreciation. First to be described are easily observable, dominant elements, to be followed by other details which can be observed by pupils and which are conditional on their psychical and emotional abilities.
Keywords: literary essay; MUSIC; folk tradition; interpretation; folklore